Pengaruh Financial Technology Dan Literasi Keuangan Terhadap Kinerja Umkm Pada Sektor Kuliner Di Kabupaten Gianyar - herawati, pande kadek; Putra, I Putu Deddy Samtika; Pratiwi, Ni Putu Trisna Windika (UNHI Press, 2025)
This study aims to test and analyze the influence of Financial Technology and Financial Literacy on the Performance of MSMEs in the Culinary Sector in Gianyar Regency. This research is quantitative, using a questionnaire for data collection and a Likert scale for measurement. The population in this study is MSMEs in the Culinary Sector in Gianyar Regency. The sampling method uses stratified random sampling with a sample of 89 respondents. Data analysis techniques use multiple regression analysis with SPSS 29. The results show that partially Financial Technology and Financial Literacy have a significant positive effect on MSME Performance. The implications of this research can be used as a basis for developing strategies to improve the performance of MSMEs through the adoption of financial technology and increasing financial literacy.